2005
DOI: 10.1097/01.ju.0000177453.14334.a2
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Andropause Symptoms in Infertile Men

Abstract: Andropause symptoms and erectile dysfunction are common among infertile men, affecting approximately 38% of this population. This finding suggests that the population of infertile men should be carefully screened to identify and treat those with erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 18 publications
4
31
1
Order By: Relevance
“…Erectile dysfunction (IIEF-15-EFD score <26) was present iñ 20% of the study cohort. This prevalence is essentially in agreement with previous reports in infertile men (Jain et al, 2000;O'Brien et al, 2005;Shindel et al, 2008;Lotti et al, 2012), but is at least double than that observed in the general Italian population, when subjects with a similar mean age are considered (Parazzini et al, 2000;Mirone et al, 2004). The prevalence of ED in our patient population was further increased by the MetS condition, with hypertension and visceral adiposity as the main determinants.…”
Section: Discussionsupporting
confidence: 81%
“…Erectile dysfunction (IIEF-15-EFD score <26) was present iñ 20% of the study cohort. This prevalence is essentially in agreement with previous reports in infertile men (Jain et al, 2000;O'Brien et al, 2005;Shindel et al, 2008;Lotti et al, 2012), but is at least double than that observed in the general Italian population, when subjects with a similar mean age are considered (Parazzini et al, 2000;Mirone et al, 2004). The prevalence of ED in our patient population was further increased by the MetS condition, with hypertension and visceral adiposity as the main determinants.…”
Section: Discussionsupporting
confidence: 81%
“…Erectile dysfunction has been correlated with male infertility. In participants who answered the Sexual Health Inventory questionnaire, 27% of infertile men reported erectile dysfunction compared with 11% of the fertile control group (66).…”
Section: Obesity and Sexual Dysfunctionmentioning
confidence: 99%
“…In the literature, several studies have reported a higher prevalence of ED in infertile male patients compared with the male general population (Jain et al, 2000;Monga et al, 2004;O'Brien et al, 2005;Shindel et al, 2008;Lotti et al, 2012;Gao et al, 2013), see Table 1 for details. Shindel et al (2008) indicated that the incidence of ED in the male infertile population (22%) was higher than that observed in a male population of the same age (7 to 9%).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%